2012
DOI: 10.1258/ar.2012.120303
|View full text |Cite
|
Sign up to set email alerts
|

An observational study to evaluate the efficiency and safety of ioversol pre-filled syringes compared with ioversol bottles in contrast-enhanced examinations

Abstract: Administration of ioversol for contrast-enhanced CT examinations is associated with a low incidence of AEs and is generally safe and well tolerated. Ioversol pre-filled syringes were associated with lower residual volumes and less potential re-use compared with bottles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Among the selected studies, 26 [ 17 , 18 , 20 38 , 40 , 42 45 ] documented the incidence of all ADRs or specifically HSRs (56,502 patients and 1,613,481 doses) and 5 studies [ 16 , 19 , 39 , 46 , 47 ] reported the incidence of PC-AKI (1335 patients). Contrast-enhanced CT was the main indication for which ioversol was used, followed by venography and urography.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the selected studies, 26 [ 17 , 18 , 20 38 , 40 , 42 45 ] documented the incidence of all ADRs or specifically HSRs (56,502 patients and 1,613,481 doses) and 5 studies [ 16 , 19 , 39 , 46 , 47 ] reported the incidence of PC-AKI (1335 patients). Contrast-enhanced CT was the main indication for which ioversol was used, followed by venography and urography.…”
Section: Resultsmentioning
confidence: 99%
“…The overall incidence of ADRs in adults was reported in 15 studies [ 17 , 20 – 26 , 28 , 29 , 32 , 33 , 35 , 42 , 43 ] with a median of 0.23%. In two studies where heat sensation was assessed in a specific questionnaire, a higher incidence of ADRs was reported (42–63%) [ 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations